Inventory Management System (IMS) / Nurul Amira Mohammad Zen - Mohammad Zen, Nurul Amira (2016)
Inventory management system is important for Z&Z Niaga Sdn. Bhd. The current system used by Z&Z Niaga Sdn. Bhd. is a manual system that concerns a lot of attention from the staff when recording and calculating the inventory. Waterfall Model was used as System Development Life Cycle Model. Started from the initial study, data collection method are important as it will contribute into analysing the problem. From the analysis, a solution which a proposed system will clearly defined as the solution for the problem. The design phase consist of the design of the system that help the developer to be more aware of what system will be develop. The step by step guidelines through each phase of the system development cycle also make the development of the system easier. The results from the system testing and evaluation done by experts and users were obtained and analyzed. It was found that IMS still need a lot of improvement especially in terms of consistency of the interface and the terms used in entire IMS. The contents of IMS also were said to be limited. Based on user’s evaluation, Learnability has a mean of 3.62 and standard deviation 0.21, Usefulness & Capabilities has a mean of 3.85 and standard deviation of 0.11. Contents has the highest mean and standard deviation which is 3.96 and 0.14 respectively. Mean for construct Efficiency, Satisfaction and Interface is 3.82, 3.84 and 3.78 respectively. The lowest standard deviation is 0.05 for Interface while standard deviation for Efficiency and Satisfaction is 0.12 and 0.09 respectively.